Railways in Transition: A Review of Five Countries - Holvad, Torben (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The organisation of passenger railways is currently undergoing significant changes in a number of countries in Europe as well as in the rest of the World. Traditionally, railways have been organised nationally as state monopolies responsible for both infrastructure and services, but recent years have seen a move away from this model. In particular, infrastructure and services have been separated in EU countries (although in other parts of the world vertical integrated railways are still present) and there have also been initiatives regarding deregulation, internationalisation and privatisation. A key motivation for initiating reforms of the railway sector in the different countries is often a perceived lack of customer orientation and the cost inefficiencies due to a lack of competitive pressure. In this paper railway reforms in five countries will be reviewed: Japan, New Zealand, United Kingdom, Sweden and Denmark. These countries cover a number of dimensions of railway reform including privately vs. publicly owned companies, vertical integration vs. vertical separation, tendering vs. no tendering.